2015
DOI: 10.1055/s-0034-1391781
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness resection in the colorectum with a novel over-the-scope device: first experience

Abstract: Background and study aims: Endoscopic full-thickness resection (EFTR) in the lower gastrointestinal tract may be a valuable therapeutic and diagnostic approach for a variety of indications. Although feasibility of EFTR has been demonstrated, there is a lack of safe and effective endoscopic devices for routine use. The aim of this study was to investigate the efficacy and safety of a novel over-the-scope device for colorectal EFTR. Patients and methods: Between July 2012 and July 2014, 25 patients underwent EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
140
3
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(169 citation statements)
references
References 24 publications
8
140
3
10
Order By: Relevance
“…En bloc-R0 resection was achieved in 29/33 patients (87.9%), which compares favorably to the results of previous studies (75%-80.6%) 19,20 as well as to the preliminary data available from the Wall Resect Study (76.6%). The overall rate of histologically proven FTR of 80.6% (colon 90.0%, rectum 63.6%) was slightly below the rate of 87.5% published by Schmidt et al This may be explained by the higher percentage of lesions located in the rectum in our study (36.4% vs 8%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…En bloc-R0 resection was achieved in 29/33 patients (87.9%), which compares favorably to the results of previous studies (75%-80.6%) 19,20 as well as to the preliminary data available from the Wall Resect Study (76.6%). The overall rate of histologically proven FTR of 80.6% (colon 90.0%, rectum 63.6%) was slightly below the rate of 87.5% published by Schmidt et al This may be explained by the higher percentage of lesions located in the rectum in our study (36.4% vs 8%).…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, this is the largest series of FTRD in consecutive patients so far. To date, four case reports [15][16][17][18] and two retrospective studies have been published, 19,20 the latter two comprising a total of 45 cases. More data are expected from the Wall Resect Study, which completed patient recruitment in April 2016 and at present provides preliminary data from 181 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A novel endoscopic full-thickness resection device (Ovesco Endoscopy, Tübin-gen, Germany) has been developed based on the combination of an overthe-scope clip with an enlarged resection cap (21 mm) and a snare preloaded in the distal rim of the cap [1,2]. We report the case of a 53-year-old woman with a history of abdominal panniculitis with fat necrosis and perivasculitis with giant cell histiocytosis.…”
mentioning
confidence: 99%
“…The feasibility and effectiveness of this procedure was shown in several case series and 2 retrospective studies, with few complications reported [4,6,7]. Recently, the results of the Wall Resect study, the first prospective multicenter trial, were published.…”
Section: Discussionmentioning
confidence: 99%